WHY PEOPLE DO NOT JOIN POLITICAL PARTIES? ANALYSING THE ATTITUDES OF LITHUANIANS TOWARDS PARTY MEMBERSHIP - Ramonaitė, Ainė (Politologija, 2015)
Partisan activity has been the main and the most important mode of institutionalized political participation (in addition to electoral participation) in the modern democracy. Even though mass party membership is a distinct feature of modern political system (although not necessarily democratic), since 1960-ies the decline of party membership is observed in many democratic countries. Lithuania is a typical example of post-communist region, where party membership is regarded as a specific elitist activity rather than an ordinary practice of political involvement. In the article, the attitudes of Lithuanians towards party membership are analyzed to answer the question if and why people are not keen to join political parties. Public attitudes are explored using the data of a representative public opinion survey carried out in 2005 and qualitative data of in-depth interviews with ordinary people collected in 2008. Using a mixed method research strategy, the article analyses the image of political parties in Lithuania, determines the potential of party membership and investigates the dominant reasons of avoiding partisan activity. In the first part of the article, the theories explaining partisan activity are presented. In addition to Civic voluntarism model and General incentives theory used by Paul Whiteley and Patrick Seyd to explain partisan activity, the broader theories explaining changes of political culture and transformation of party models are discussed. Moreover, the theoretical arguments for the exceptionalism of post-communist societies are presented. In the second part of the article, the analysis of the qualitative data is presented. The exploration of public attitudes reveals that partisan activity can be perceived in several different ways: as a specific occupation, as a civic self-expression, as belonging to power elite, as a privilege, as dependence, and as partiality. These images of parties held by people are related to their attitudes towards party membership. The reasons provided by the people of not joining political parties can be grouped into three groups: 1) the lack of necessary resources or personal characteristics (e.g. old age, low education, etc.); 2) critical attitudes towards political parties; 3) dislike of partisan activity because of indifference towards politics or individualism and appreciation of personal independence. In the third part, the quantitative data drawn from the public opinion survey isanalysed. The data shows a surprisingly high potential of party membership in Lithuania: about 11 percent of all respondents and about 20 percent of respondents in the age group of 18–39 have an inclination to join a political party. However, 87 percent of individuals admit that they were not invited to join a political party during the last 5 years. This proves that Lithuanian political parties are not active in expanding their membership. The quantitative data approve the trends observed from the qualitative research. The two most popular reasons of not joining a party are the lack of resources or necessary characteristics (surprisingly, young age seems to be one of the most important of them) and an indifference towards politics. These two motives fit well into the Civic voluntarism model. Disappointment with politics or a negative attitude towards political parties in general, contrary to expectations, proved to be of secondary importance. The importance of individualist attitudes, i.e. the avoidance of commitment and appreciation of independence, unfortunately, could not be evaluated due to the lack of data. Summing up, the analysis of Lithuanian case suggests that low party membership in post-communist countries might be explained by low demand rather than low supply. In other words, we should look for the explanation of low enrolment in the process of recruitment of party members rather than in the attitudes of people. The research do not provide any evidence for a popular theory of “communist legacy” claiming that a “bad” image of parties inherited from communist regime accounts for the low party membership in post-communist societies. On the contrary, the data demonstrate rather positive attitudes towards partisan activity among Lithuanian population.